FRI0349 Exploring Symptom Duration, Auto Antibodies and Inflammation in Order to Explain the Predictive Value of Baseline Erosions for Future Structural Damage in Rheumatoid Arthritis. (10th June 2014) - van Nies, J.A.; van Steenbergen, H.W.; Krabben, A.; Stomp, W.; Huizinga, T.W.; Reijnierse, M.; van der Helm-van Mil, A.H.
Abstract : Background: Baseline erosions are characteristic for Rheumatoid Arthritis (RA) and predictive for the severity of structural damage during the disease. The mechanisms leading to baseline erosions being a strong predictor for radiological progression are unknown. Objectives: We aimed to increase this understanding. We therefore explored several hypotheses in an observational cohort study and a cross-sectional MRI-study. First, it was presumed that patients with baseline erosions are more advanced in their disease, reflected by a longer symptom duration. This means that baseline erosions could act as a mediator between the symptom duration at baseline and radiological damage over time. Furthermore, patients with baseline erosions might represent a more severe disease subset that is characterized by the presence of auto-antibodies. Alternatively, patients with baseline erosions might have more inflammation (systemic or local), which drives the association between baseline erosions and joint damage over time. Methods: 3, 256 Hands and feet radiographs of 653 early RA-patients assessed during 7-years of disease were scored using the Sharp-van der Heijde-method. Multivariate regression analyses and mediation models 1 were used to explore the association between baseline erosions, symptom duration, ACPA, RF, swollen joint counts, acute phase reactants and radiological damage over time. We also investigated whether baseline erosions were associated with local MRI detected subclinical inflammation in a second dataset of 67 RA-patients whom underwent a 1.5T MRI and had hands and feet radiographs at baseline. Here 603 joints (MCP2-5 and MTP1-5) were scanned and scored according to RAMRIS. Data on MRI-inflammation were compared with clinical inflammation and baseline radiological erosions. Results: Patients with baseline erosions had, at any point in time during 7-years, 3.45 times more joint damage than patients without erosions (p<0.001, 95%CI 3.00-3.98). Baseline erosions were an independent predictor in the multivariate regression analysis. Mediation analyses revealed that baseline erosions were not a mediator between symptom duration, systemic or local clinical inflammation (ESR, SJC) or auto-antibodies (ACPA, RF) and radiological damage. Subclinical MRI-inflammation was studied in relation to erosions, revealing that 83% of the non-swollen joints with baseline erosions had subclinical MRI-inflammation compared to 25% of the non-swollen joints without baseline erosions (OR 15.2 95%CI 3.1-102.1). The association between MRI-inflammation and baseline erosions was independent of symptom duration, ESR, SJC and auto-antibodies. Conclusions: Baseline erosions are a predictor for future joint damage, independent of known predictors as time, auto-antibodies or clinical measurable inflammation. Subclinical inflammation is suggested as an underlying mechanism. References: Baron RM, Kenny DA. The moderator-mediator variable distinction in social psychological research: conceptual, strategic, and statistical considerations. J Pers Soc Psychol 1986;51(6):1173-82. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1457